2021
DOI: 10.1155/2021/5522964
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis Induced by Ziziphora tenuior Essential Oil in Human Colorectal Cancer Cells

Abstract: Ziziphora (Cacotti in Persian) belongs to the Lamiaceae family (mint group) and is vastly found in Iran and Asia. This traditional medicinal plant is normally used as analgesic and for treatment of particular gastrointestinal diseases. Since colorectal cancer is one of the most common causes of death in the world and the second leading cause of cancer death among adults, there is a pressing need to inhibit this malignancy by using methods with minimal side effects. One of these methods is the use of natural re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…After that, the membrane was washed three times with TBST and the secondary antibody (1 : 1000) was added to be incubated for 1 h and washed with TBST. Then, band intensities were detected using the chemiluminescent substrate Supersignal Femto kit and band densities were analyzed using the ImageJ 1.52a program (Bethesda, Maryland, USA) [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…After that, the membrane was washed three times with TBST and the secondary antibody (1 : 1000) was added to be incubated for 1 h and washed with TBST. Then, band intensities were detected using the chemiluminescent substrate Supersignal Femto kit and band densities were analyzed using the ImageJ 1.52a program (Bethesda, Maryland, USA) [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…As an example, Duymus et al [ 69 ] reported the EO from Vitex agnus-castus L. fruit, enriched in 1,8-cineole, showed high apoptotic activity against both A549 (human lung adenocarcinoma cells) and MCF-7 cells [ 69 ]. Another work stated that treatment with Ziziphora tenuior L. EO (with a high content in pulegone) on colorectal cancer epithelial cells (HT-29) revealed a time-dependent apoptosis mechanism [ 70 ]. It is worth mentioning that the reason for these apoptotic events in these studies seems to be due to the rich content in camphor and pulegone from L. pedunculata and M. cervina , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…According to Harley et al, [14] Pamir Most of them are source of biologically active compounds and used as antioxidant, antiseptic, immunomodulatory, antimicrobial in traditional medicine and pharmaceutics. Thus, Ziziphora [15][16][17], Salvia [18], Hymenocrater [19], Dracocephalum [20] and other represents of Lamiaceae characterized by a high content of polysaccharides, polyphenols, alkaloids and other carbohydrates [21][22][23].…”
Section: Resultsmentioning
confidence: 99%
“…8 taxa of Ziziphora are named for the territory of Uzbekistan. Its species are of prime importance in different fields of pharmaceutical, chemical, medicinal, traditional and folk medicines [15][16][17].…”
Section: Resultsmentioning
confidence: 99%